An expedition to identify and fix objects intangible ethnocultural heritage in the Komi Republic - Druzhinina , I.S; Nikonov, V.V. (Perm Federal Research Centre Journal, 2026)
The article presents the results of a folklore and ethnographic expedition conducted in 2025 in the Izhemsky district of the Komi Republic. The purpose of the work was to identify, record and document objects of intangible ethnocultural heritage of the Komi-Izhemians, a subethnic group of the Komi people. The article describes field materialscollected in the settlements of Izhma, Gam, Sizyabsk, Mokhcha, etc. The focus is on key heritage sites: the folk festival “Lud”, the song tradition, including ritual lamentations, and the traditional Izhma women’s costume. The current state of these phenomena, their manifestration in the activities of folklore groups and their role in preserving cultural identity are profiled in the article.